UNESCO CHAIR ON LIFELONG PROFESSIONAL EDUCATION IN THE XXI CENTURY OF THE NAES OF UKRAINE: STRATEGIC DIRECTIONS OF DEVELOPMENT - Галина Сотська (Ivan Ziaziun Institute of Pedagogical Education and Adult Education of the NAES of Ukraine, 2020)
The article outlines the strategic goal of the UNESCO Chair on Lifelong Professional Educa-tion in the XXI Century of the National Academy of Educational Sciences of Ukraine. The main tasks of the Chair are as follows: to promote the creation of an educational platform for the exchange of knowledge and best practices by organizing and conducting events, creating a database and a special web site, preparing and distributing publications, including online; consolidation of the community of teachers, researchers and students in the field of professional and pedagogical education as well as adult education; dissemination of knowledge and support in the development and implementation of national strategies and plans for profes-sional training and adult education throughout life; to establish cooperation with other UNESCO Chairs with-in the framework of corresponding programs and activities. The information on the organization and hold-ing by the Chair of scientific and practical mass events aimed at the development of international academic and scientific solidarity (webinar "Mother language and multilingual education in the context of sustainable development", round table "T.H. Shevchenko's Civic and Patriotic Ideas in the Socio-Cultural and Educational Space of Ukraine", the scientific-practical conference "Museum Pedagogy: Problems, Present, Prospects", etc.) has been revealed. This contributed to the intensification of the knowledge exchange among the world's uni-versities, strengthening inter-chair coordination, increasing network collaboration, expanding partnerships and setting up joint platforms for interdisciplinary dialogue with the support of the UNITWIN / Chair Coor-dinating Board in Ukraine. The prospects for further activity of the Chair are determined, in particular: ex-pansion of cooperation with international and national experts in the spheres of education, science and cul-ture; assistance to staff and graduate students of the Institute in obtaining grants for educational, research and cultural projects; strengthening of educational and cultural initiatives in adult education; conducting events aimed at raising the level of quality of scientific and pedagogical staff training by increasing the num-ber of international projects with foreign partners, within which staff, graduate students and doctoral stu-dents of the Institute will have the opportunity to undergo study / internship in foreign educational institu-tions through academic mobility programs.